2021
DOI: 10.3390/ijms221910636
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Respiratory Tract of Felids Is Highly Susceptible to SARS-CoV-2 Infection

Abstract: Natural or experimental infection of domestic cats and virus transmission from humans to captive predatory cats suggest that felids are highly susceptible to SARS-CoV-2 infection. However, it is unclear which cells and compartments of the respiratory tract are infected. To address this question, primary cell cultures derived from the nose, trachea, and lungs of cat and lion were inoculated with SARS-CoV-2. Strong viral replication was observed for nasal mucosa explants and tracheal air–liquid interface culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Another study suggested that the SARS-CoV-2 M protein induces motility, proliferation, stemness, and in vivo metastasis of triple-negative breast cancer [ 111 ]. Despite studies reporting that SARS-CoV-2 could also infect felids [ 113 ], dogs [ 114 ], and many other domestic species [ 115 ], reports on dogs or other pets exhibiting a SARS-CoV-2-induced EMT process are still lacking.…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…Another study suggested that the SARS-CoV-2 M protein induces motility, proliferation, stemness, and in vivo metastasis of triple-negative breast cancer [ 111 ]. Despite studies reporting that SARS-CoV-2 could also infect felids [ 113 ], dogs [ 114 ], and many other domestic species [ 115 ], reports on dogs or other pets exhibiting a SARS-CoV-2-induced EMT process are still lacking.…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…Most of these cases do not present clinical signs or only display with mild upper respiratory clinical signs (Barroso-Arévalo et al, 2022;Hosie et al, 2021;Klaus et al, 2021). Generally, the susceptibility of cats to SARS-CoV-2 infection is thought to be related to the expression of cognate viral receptor ACE2 in the upper respiratory tract (Färber et al, 2022;Gerhards et al, 2021;Krüger et al, 2021;Lean et al, 2021). Similar observations have also been made from in vivo modelling of SARS-CoV-2 infection in cats (Bosco-Lauth et al, 2020;Gaudreault et al, 2020).…”
Section: Introductionmentioning
confidence: 63%
“…Why only nasal discharge was present without other signs of respiratory infection could be due to the difference in the receptor ACE2 expression across tissues, as in lion, cheetah and lynx [28]. While recognition of the receptor ACE2 is a key determining factor for cross-species infection of SARS-CoV-2, the transmembrane serine protease 2 (TMPRSS2) is also important to cleave the spike protein and facilitate viral-host membrane fusion.…”
Section: Discussionmentioning
confidence: 99%